Dampak Penggunaan Quick Response Code Indonesia Standard (Qris) Terhadap Usaha Mikro Kecil Menengah (Umkm) Kecamatan Tanete Rilau Kab. Barru Sulawesi Selatan - Fini Fitriah; Andi Rustam; Muhaimin (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2025)
This research is a type of quantitative research with the aim of determining the impact of the Quick Response Code Indonesia Standard (QRIS) payment system on MSMEs in Barru Regency, Tellumpanua Village, and to determine the obstacles to implementing the QRIS payment system on MSMEs in Barru Regency, Tellumpanua Village. This sample was taken from the BRI Bank branch, Tanete Rilau District, Barru Regency, South Sulawesi. with a population of 103 MSMEs and a sample of 51 MSMEs. In this study, the data sources used in data collection include prime data. Instruments Based on the results of data research using statistical calculations through the SPSS Version 27 application, that partially the results show that the use of the Quick Response Code Indonesian Standard (QRIS) has a positive and significant effect on the ease of MSME transactions in Tanete Rilau District, Barru Regency. it is concluded that there is a positive and significant impact on the ease of MSME transactions